Analisis Hubungan Kualitas Pelayanan dan Fasilitas dengan Kepuasan Pasien di Puskesmas Selogiri Kabupaten Wonogiri - Anisa Dwi Anggraini; Indra Hastuti; Adam Sasando (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Community Health Centers (Puskesmas) serve as primary healthcare facilities with a strategic role in delivering quality services and adequate infrastructure to the public. However, patient complaints are still frequently found, particularly concerning suboptimal service aspects such as unprofessional staff attitudes and uncomfortable waiting areas. This study aims to examine the relationship between service quality and facilities on patient satisfaction at Puskesmas Selogiri, Wonogiri Regency. The research employed a quantitative associative method with a survey approach. A total of 100 respondents were selected using purposive sampling. Data were collected through questionnaires and analyzed using the Spearman Rank test due to the non-normal distribution of the data. The findings revealed a very strong and positive correlation between service quality and patient satisfaction, with a correlation coefficient of 0.906. Similarly, facilities also showed a strong and significant relationship with patient satisfaction, with a correlation coefficient of 0.850. These results imply the importance of improving service interaction quality and providing comfortable facilities to enhance positive patient experiences and strengthen public trust in the services delivered by Puskesmas.